Tissue Oxygen Demand in Regulation of the Behavior of the Cells in the Vasculature. (9th August 2013) - Barvitenko, Nadezhda N.; Aslam, Muhammad; Filosa, Jessica; Matteucci, Elena; Nikinmaa, Mikko; Pantaleo, Antonella; Saldanha, Carlota; Baskurt, Oguz K.
Abstract The control of arteriolar diameters in microvasculature has been in the focus of studies on mechanisms matching oxygen demand and supply at the tissue level. Functionally, important vascular elements include EC, VSMC, and RBC. Integration of these different cell types into functional units aimed at matching tissue oxygen supply with tissue oxygen demand is only achieved when all these cells can respond to the signals of tissue oxygen demand. Many vasoactive agents that serve as signals of tissue oxygen demand have their receptors on all these types of cells (VSMC, EC, and RBC) implying that there can be a coordinated regulation of their behavior by the tissue oxygen demand. Such functions of RBC as oxygen carrying by Hb, rheology, and release of vasoactive agents are considered. Several common extra‐ and intracellular signaling pathways that link tissue oxygen demand with control of VSMC contractility, EC permeability, and RBC functioning are discussed.